República Argentina, Océano Atlántico Sur, Islas Georgias del Sur / compilación de levantamientos nacionales y extranjeros - Argentina. Ministerio de Marina; Argentina. Ministerio de Guerra y Marina; Argentina. Secretaría de Marina (Argentina. Ministerio de Marina, 1952)
1a edición 1952 Relief shown by spot heights and hachures. Depths shown by soundings. Includes tidal, conversion and name tables and 1 inset map: Rocas Cormoran y Negra. Selected lights shown in purple. "L.J. Sejas Cartógrafo" -- lower right margin. "114." Color; 1:350,000